2010
DOI: 10.1177/0148607110362529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Free Fatty Acids on Bilirubin–Albumin Binding Affinity and Unbound Bilirubin in Premature Infants

Abstract: Background The author has previously shown that intravenous lipid intake may be associated with an increase in unbound bilirubin in infants ≤28 weeks gestational age. The objective of this study was to evaluate whether this increase in unbound bilirubin is mediated by free fatty acids and to examine the secondary effect of free fatty acids on bilirubin–albumin binding affinity. Methods A prospective study was conducted to include 26 infants ≤32 weeks gestational age with indirect hyperbilirubinemia and recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…Neonatal HSA concentrations depend on gestational age, ranging from 280 to 470 mol/L (30 ). In neonates receiving Intralipid, FFA concentrations increase severalfold, resulting in substantial displacement of bilirubin from HSA and, therefore, large increases in B f concentrations (23,26,27 ). This variability in bilirubin-binding capacity can result in patients having similar plasma B T but different B f .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal HSA concentrations depend on gestational age, ranging from 280 to 470 mol/L (30 ). In neonates receiving Intralipid, FFA concentrations increase severalfold, resulting in substantial displacement of bilirubin from HSA and, therefore, large increases in B f concentrations (23,26,27 ). This variability in bilirubin-binding capacity can result in patients having similar plasma B T but different B f .…”
Section: Discussionmentioning
confidence: 99%
“…The adult-neonate difference in rate constants is still unexplained but might be related to FFA-albumin interactions (33 ). Neonates have higher plasma FFA concentrations than adults, and this may promote bilirubin dissociation leading to increased B f (19,22,23,27 ). Infusion of intralipid may reduce the 375-nm excitation intensity through increased light scattering and might yield erroneously high B f values by BL22P1B11 but not BL22P1B11-Rh.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Although the impact of endogenous FFA has not been assessed directly, increased FFA has bilirubin displacing effects, especially in premature newborns receiving intravenous lipid supplementation for nutrition and growth. 7,9,10,28,33 At an FFA/Alb ratio 54, FFAs compete with bilirubin at the bilirubin binding site, resulting in the displacement of bilirubin. 7,8,10,27,28 We found that endogenous FFAs did not affect Alb binding of bilirubin, resulting in elevations of UB, since none of the sera, from both term and preterm infants, had FFA/Alb ratios 54.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Serum UB concentrations depend not only on serum TB and Alb concentrations, but on the bilirubin-albumin binding affinity and the presence of displacers like free fatty acids (FFAs). [6][7][8][9][10] FFAs affect bilirubin-albumin binding. Briefly, Alb contains a primary high-affinity site for bilirubin and a secondary low-affinity site.…”
mentioning
confidence: 99%
See 1 more Smart Citation